How Talent Development Management in Public Sector? - Isra Misra Misra; Sardimi; Ali Sadikin; Aditya Achmad Rakim (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
Public sector services is a very relevant issue today. All countries compete to provide the best service for their people. Services have shifted from conventional-based services to digital-based services. This research is an exploratory qualitative research with a secondary data approach where the researcher wants to see a problem with nine maps of talent development management. The results of the study found that the public sector service strategy in Indonesia in the Perspective of Talent Development Management (TDM) has been running but still has a tendency to be limited according to organizational needs based on the roadmap for the concept of talent development management. The leadership commitment has the same vision so that improving the quality of public services is an obligation for public officials which is a challenge for Indonesia. Factors supporting employee talent development are consistency, cooperation, willingness, partnership, motivation and support from the community. While the inhibiting factors for employee talent development program activities are regulations, budget, supporting facilities/infrastructure and geographical location.